A view on the place and role of blood genetic systems in the etiopathogenesis of caries - Kolenko Ю. Г.; Zelinska Н. А.; Tkach О. Б. (Actual Dentistry, 2024)
Relevance. Dental caries remains one of the most common diseases in humans, and is second only to cardiovascular diseases. This is due to the lack of a clear understanding of the etiopathogenetic cause and effect relationships. Objective: to determine the place of competence of genetic markers of biological substances of blood and saliva in the etiopathogenesis of caries. Materials and methods. The study of group-specific blood factors as possible genetic markers of dental caries was carried out in 916 people. The determination of genetic markers in blood and saliva was performed in the hemagglutination reaction. Results of the study. It was found that the risk of dental caries is quite high in Bα(III) carriers. It was found that the presence of B antigen in saliva can be considered a risk factor. We have established a correlation between dental caries and the presence of Lewis antigens in saliva. In general, the following genotypes were classified as ‘critical’: Le(a–b+) P1+ , Le(a–b–)P1+ , Le(a–b+)M, Rh+(D)M, MR1+ , MR1–, Rh+ P1+ , Rh– P1+ . The protective combinations of erythrocyte antigens included the phenotypes Le(a+b–), Le(a–b+)P1–, Le(a–b–)P1–, L(a+b–)Rh+, Le(a+b–)MN, Le(a–b–)N, Rh+MN, P1–MN, Rh+P1–, Le(a–b+)N, P1–N, which were 2 4 times less frequent in patients with dental caries. Conclusions. The genophenotypes and their associations contributing to, counteracting and not affecting the development of caries were identified. The data obtained make it possible to scientifically form risk groups to obtain a special treatment and preventive approach to different categories of people. The data obtained made it possible to understand the occurrence and development of caries disease in a different way and to see the importance of immunogenetic studies in cariesology.